New Sights Into Long Non-Coding RNA LINC01133 in Cancer - Jiang, Shengnan; Zhang, Qian; Li, Jiaqi; Raziq, Khadija; Kang, Xinyu; Liang, Shiyin; Sun, Chaoyue; Liang, Xiao; Zhao, Di; Fu, Songbin; Cai, Mengdi (Frontiers in Oncology, 2022)
LINC01133 is a long intergenic non-coding RNA that regulates malignancy in several cancers, including those of the digestive, female reproductive, respiratory, and urinary system. LINC01133 is an extensively studied lncRNA that is highly conserved, and its relatively stable expression is essential for its robust biological function. Its expression is highly tissue-specific with a distinct subcellular localization. It functions as an oncogene or a tumor suppressor gene in different cancers via multiple mechanisms, such as those that involve competing with endogenous RNA and binding to RNA-binding proteins or DNA. Moreover, the secretion and transportation of LINC01133 by extracellular vesicles in the tumor micro-environment is regulated by other cells in the tumor micro-environment. To date, two mechanisms, an increase in copy number and regulation of transcription elements, have been found to regulate LINC01133 expression. Clinically, LINC01133 is an ideal marker for cancer prognosis and a potential therapeutic target in cancer treatment regimes. In this review, we aimed to summarize the aforementioned information as well as posit future directions for LINC01133 research.